Culture Influence on Managerial Discretion and the Implications for National Competitiveness - Haj Youssef, Moustafa (2017)
Studying managerial discretion, research on its national-level antecedents and implications remains scarce. We further develop the national-level construct of managerial discretion by empirically investigating the influence of cultural practices and their variations on CEOs’ discretion and its consequent implications across 15 countries. We find that cultural practices-– individualism, power distance, future, humane, and performance orientations, along with gender egalitarianism and assertiveness–and the degree of variation surrounding each of these are associated with the degree of managerial discretion. In turn, we conduct a multilevel regression analysis on a panel dataset spanning 17 years of national competitiveness levels to empirically demonstrate the direct influence of managerial discretion on national competitiveness. Finally, we show that managerial discretion mediates the relationship between cultural practices and national competitiveness.